Physical Characteristics, Phytochemical Contents and Antioxidant Activity of Ten Organic-Pigmented Rice Varieties from Surin Province - Kammapana, Laddawan (Trends in Sciences, 2023)
The objective of this study was to investigate the physical characteristics, phytochemical contents, and antioxidant activity of 10 organic-pigmented rice varieties including Tubtim Chumpae, Niaw Daeng, Nieng Guang, Mali Daeng, Hom Nil, Niaw Dam, Riceberry, Mali Gomain Surin, Malinil Surin, and Pa Ga Am Puen (obtained from Tapthai organic villages, Tha-mo, Prasat, Surin province, Thailand in June, 2021). The physical characteristics investigated included grain length, width, shape, and color in both paddy and unpolished rice. The results revealed that the mean length and width of paddy rice grain varieties ranged from 6.58 to 10.85 mm and 2.12 to 3.27 mm, respectively, while the length and width of unpolished rice grain were 5.94 to 7.53 mm and 1.74 to 2.61 mm, respectively. Most organic-pigmented rice varieties had a slender shape except for Nieng Guang and Niaw Dam, which were moderately shaped. There were 5 colors of paddy rice, including straw, purple, purple straw, black and black furrow on straw background and light purple straw while unpolished rice showed red, dark purple, black, purple, and light brown color. The anthocyanin content, total phenolic compounds and antioxidant activity of different rice varieties showed a significant difference in the range of 4.38 to 77.96 mg/100 g DW, 42.94 to 341.19 mg GAE/100 g DW and 2.71 to 34.77 mM TE/100 g DW, respectively. Niaw Dam exhibited the highest anthocyanin concentrations. The highest total phenolic content was found in Mali Daeng and Nieng Guang, resulting in high antioxidant activity. This study suggested that pigmented rice is rich in phytochemicals and antioxidants. Nieng Guang, in particular, could be promoted for cultivation and beneficial use in the food, pharmaceutical, and cosmetic industries. HIGHLIGHTS Surin province is one of the principal regions with diverse indigenous and commercial rice varieties in Thailand The grain shape of eight varieties of rice, including Tubtim Chumpae, Niaw Daeng, Mali Daeng, Hom Nil, Riceberry, Mali Gomain Surin, Malinil Surin and Pa Ga Am Puen were slender while that of Nieng Guang and Niaw Dam varieties were moderate. The physical aspects of rice indicate its quality, market value and have essential role in selecting, handling, storing, and processing of rice Niaw Dam black rice had a high content of anthocyanin while Mali Daeng and Nieng Guang red rice had the highest content of total phenols, resulting in higher antioxidant activity than the other Pa Ga Am Puen brown rice had the lowest anthocyanin content, total phenolic content and antioxidant activity The basic information of this study might be useful for selecting rice varieties for future rice breeding and provide pigmented rice nutrition information especially indigenous pigmented rice which has potential in the food, pharmaceutical and cosmetic industries GRAPHICAL ABSTRACT